1987
DOI: 10.1002/marc.1987.030080111
|View full text |Cite
|
Sign up to set email alerts
|

Reversible digital and holographic optical storage in polymeric liquid crystals

Abstract: Liquid-crystalline side chain polymers have recently been used to store optical data by a local optical heating of a preoriented polymer film into the isotropic phase. The resulting macroscopically unoriented light scattering spots were frozen-in by subsequent cooling. This technique is referred to as thermorecording'**).In our studies we found a completely different method for optical data storage in liquid-crystalline polymers. It consists in inducing optically a birefringence pattern in a layer of such a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
253
0
4

Year Published

1994
1994
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 599 publications
(262 citation statements)
references
References 7 publications
5
253
0
4
Order By: Relevance
“…The stable POA was observed later on in polymers containing chemically linked azochromophores (azopolymers) [4]. It turned out that stable anisotropy can be induced in both amorphous and liquid crystalline (LC) azopolymers [4,5,6,7,8,9,10]. The efficiency of POA in LC azopolymers is generally much higher than it is for amorphous homologues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stable POA was observed later on in polymers containing chemically linked azochromophores (azopolymers) [4]. It turned out that stable anisotropy can be induced in both amorphous and liquid crystalline (LC) azopolymers [4,5,6,7,8,9,10]. The efficiency of POA in LC azopolymers is generally much higher than it is for amorphous homologues.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years this spatial character of the photoinduced anisotropies has not received much attention and, until recently, it has been neglected in the bulk of experimental and theoretical studies of POA in azobenzene containing polymers [4,12,13,14,19,20,21,22,23,24]. On the other hand, the problems related to the 3D orientational structures in polymeric films are currently of considerable importance in the development of new compensation films for liquid crystal (LC) displays [25] and the pretilt angle generation by the use of photoalignment method of LC orientation [26].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon was very unstable, decaying almost immediately as the laser was switched off. Independently, in 1987, Ringsdorf et al (8) reported a similar phenomenon in liquid crystalline side-chain polymers. The polymer sample was a film which was initially subjected to an electric field to obtain a general director for the nematic or smectic organization of the azobenzene groups.…”
Section: Background and Previous Literaturementioning
confidence: 80%
“…For example, potential applications are patterned polarization rotators for stereoscopic displays, optical data storage, polarization sensitive gratings or polarization sensitive recordings, and holograms for copy protection. [1][2][3][4][5][6][7] More recently, much attention is given towards local control of the alignment of liquid crystals in multidomain liquid crystal displays for the improvement of the viewing angle. [8][9][10] In general, the liquid crystal ͑LC͒ orientation can be influenced via modification of the bulk LC orientation or, indirectly, via modification of the alignment layer.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of the transmission of liquid crystal layers between crossed polarizers via directly influencing the bulk orientation of liquid crystals has been shown to be possible using polarized light illumination of LC layers containing dyes. [3][4][5] The dye has to be anisotropic and photoisomerizable. Due to the absorption of light, the dye undergoes repeated trans to cis and cis to trans isomerizations.…”
Section: Introductionmentioning
confidence: 99%